What are the best approaches to management of chronic scapholunate dissociation?. Issue 4 (April 2017) - Daul, Morgan; Moss, Barbara Ann
Abstract : EVIDENCE‐BASED ANSWER : The first step is staging of injuries by evaluation of the ligaments, alignment, reducibility of the carpal bones, and development of arthritis. Arthroscopic debridement and electrothermal shrinkage is associated with good outcomes for less severe injuries, whereas severe injuries are often treated with capsulodesis and tenodesis (SOR: C, systematic reviews of small case series).